Employment regulations through the eyes of employers : do they matter and how do firms respond to them? - Pierre, Gaëlle (Policy research working paper, 2004)
"Pierre and Scarpetta present evidence on how employers perceive labor regulations and react when these are perceived to constrain the operation of their firm. They draw from harmonized surveys of (up to) 17,000 firms around the world and compare employers' responses with actual labor legislation. The authors find that employers' concerns about labor regulations are closely matched by the relative stringency of de jure labor laws. Countries that have, from an international perspective, tight labor regulations tend to have higher proportions of employers reporting these regulations as severe constraints. But not all firms are affected in the same way by onerous labor regulations. Medium sized firms are those whose business and prospects for growth are most negatively affected. Similarly, innovating firms are disproportionally affected by tight labor regulations. There is also clear evidence in the data that firms facing tight regulations invest more in training and make greater use of temporary employment. Small firms mainly rely on temporary employment, while medium and large firms, as well as innovating firms, tend to rely more on on-the-job training if labor regulations make hiring and firing very costly. This paper--a product of the Division, Human Development Network--is part of a larger effort in the network to understand the effect of employment regulations on firm's performance"--World Bank web site